Implantable collamer lens for residual refractive error after corneal refractive surgery - Chen, Xun (Int J Ophthalmol, 2016)
AIM: To assess the safety, efficacy, predictability and stability of implantable collamer lens (ICL) for residual refractive error after corneal refractive surgery. METHODS: This study evaluated 19 eyes of 12 patients who underwent ICL implantation after corneal refractive surgeries. They were followed up for 1y to 5y of uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), manifest refractive error, flat and steep K value, axial length, intraocular pressure, corneal endothelial cell density, adverse events after ICL surgery. RESULTS: The mean follow-up period was 39.05±19.22 mo (range, 1-5y). Spherical equivalent refractive error changed from -7.45±3.02 D preoperatively to -0.85±1.10 D 1wk to 1mo after ICL implantation, with the safety and efficacy indices being 1.12 and 1.15, respectively. A total of 52.63% of eyes were within ±0.5 D of the predicted spherical equivalents, 73.68% were within ±1.0 D. A trend of mild regression towards myopia with axial elongation after 5y was observed. One eye with mild anterior capsule opacity and retinal detachment 1y after surgery were observed. CONCLUSION: ICL implantation is safe and effective for the correction of residual refractive error after corneal refractive surgeries, especially in moderate to high residual myopia.